Moffett's Corner Introduction - Stephen Lafer; Jonathan M. Marine (Journal of the Assembly for Expanded Perspectives on Learning, 2024)
In this special edition of Moffett’s Corner, Sheridan Blau, former Professor of Practice in the teaching of English at Teachers College, Columbia University interviews the noted composition theorist Sondra Perl in order to solicit her memories of the late James Moffett.
Keywords: Moffett